Curbing the COVID-19 pandemic with facility-based isolation of mild cases: a mathematical modeling study - Chen, Simiao; Chen, Qiushi; Yang, Juntao; Lin, Lin; Li, Linye; Jiao, Lirui; Geldsetzer, Pascal; Wang, Chen; Wilder-Smith, Annelies; Bärnighausen, Till (Journal of travel medicine, 2021)
In many countries, patients with mild coronavirus disease 2019 (COVID-19) are told to self-isolate at home, but imperfect compliance and shared living space with uninfected people limit the effectiveness of home-based isolation. We examine the impact of facility-based isolation compared to self-isolation at home on the continuing epidemic in the USA.We developed a compartment model to simulate the dynamic transmission of COVID-19 and calibrated it to key epidemic measures in the USA from March to September 2020. We simulated facility-based isolation strategies with various capacities and starting times under different diagnosis rates. Our primary model outcomes are new infections and deaths over 2 months from October 2020 onwards. In addition to national-level estimations, we explored the effects of facility-based isolation under different epidemic burdens in major US Census Regions. We performed sensitivity analyses by varying key model assumptions and parameters.We find that facility-based isolation with moderate capacity of 5 beds per 10 000 total population could avert 4.17 (95% credible interval 1.65-7.11) million new infections and 16 000 (8000-23 000) deaths in 2 months compared with home-based isolation. These results are equivalent to relative reductions of 57% (44-61%) in new infections and 37% (27-40%) in deaths. Facility-based isolation with high capacity of 10 beds per 10 000 population could achieve reductions of 76% (62-84%) in new infections and 52% (37-64%) in deaths when supported by expanded testing with an additional 20% daily diagnosis rate. Delays in implementation would substantially reduce the impact of facility-based isolation. The effective capacity and the impact of facility-based isolation varied by epidemic stage across regions.Timely facility-based isolation for mild COVID-19 cases could substantially reduce the number of new infections and effectively curb the continuing epidemic in the USA. Local epidemic burdens should determine the scale of facility-based isolation strategies.
Published: 03 December 2020
Gesehen am 18.05.2021